Hydraulic conductivity reduction of poorly graded sand by bentonite - ปริวัตรพันธ์, สหัสชัย (Srinakharinwirot University Engineering Journal, 2020)
The main focus of this research is a study of the hydraulic conductivity of poorly graded sand by mixing with bentonite. The poorly graded sand found in the Pachi Basin are characterized by a high degree of leakage. The laboratory tests of the poorly graded sand samples resulted in a hydraulic conductivity of 119.2 mm/day and 23.16 mm/day at the bulk density of 1.69 g/cm3 and 2.25 g/cm3, respectively. The results also show that as bentonite ratios, bulk density, and curing period increase, the hydraulic conductivity is decreased. When bentonite was mixed with poorly graded sand and cured for 1 day, the hydraulic conductivity was 0.81, 0.42, 0.18 mm/day at bulk density 2.01-2.08 g/cm3 with bentonite content of 5%, 7%, and 9%, respectively. The study also found that all tested samples of bentonite poorly graded sand have acceptable hydraulic conductivity to be used in ponds. Except for soil with 5% and 7% bentonite content by weight, this is not cured and not compacted before use. This research also presents the equation for design of the bentonite ratio as an ingredient in sandy soils for another case.